Supporting Active User Involvement in Prototyping - Grønbæk, Kaj (DAIMI Report Series, 1990)
The term prototyping has in recent years become a buzzword in both research and practice of systems design due to a number of claimed advantages of prototyping techniques over traditional specification techniques. In particular it is often stated that prototyping facilitates the users’ involvement in the development process. But prototyping does not automatically imply active user involvement! Thus a cooperative prototyping approach aiming at involving users actively and creatively in system design is proposed in this paper. The key point of the approach is to involve users in activities that closely couple development of prototypes to early evaluation of prototypes in envisioned use situations. Having users involved in such activities creates new requirements for tool support. Tools that support direct manipulation of prototypes and simulation of behaviour have shown promise for cooperative prototyping activities. Examples of such tools are given and the ways that they support cooperative prototyping within various use domains are discussed.